Susceptibility‐guided quadruple therapy is not superior to medication history‐guided therapy for the rescue treatment of Helicobacter pylori infection: A randomized controlled trial - Ji, Chao Ran; Liu, Jing; Li, Yue Yue; Qiao, Chen; Qu, Jun Yan; Hu, Jun Nan; Lin, Min Juan; Ji, Rui; Li, Li Xiang; Zuo, Xiu Li; Li, Yan Qing (Journal of digestive diseases, 2020)
Objective In this study we aimed to compare the efficacy and safety of two personalized rescue therapies for Helicobacter pylori infection. Methods An open‐label, single‐center, randomized controlled trial was conducted. Patients who had failed one or two regimens for H. pylori infection were randomized to receive a 14‐day bismuth‐containing quadruple therapy guided by antimicrobial susceptibility testing (AST) or personal medication history (PMH). In the AST group, either two of amoxicillin, clarithromycin, metronidazole or levofloxacin were prescribed according to the AST. In the PMH group, amoxicillin plus either levofloxacin or furazolidone were prescribed based on the patient's history of quinolone use. The primary outcomes were eradication rates confirmed by an urea breath test 6 weeks after treatment. The secondary outcomes were adherence, incidence of adverse events (AE) and cost‐effectiveness. Results Altogether 164 with a positive culture received AST‐guided therapy and 192 received PMH‐guided therapy, respectively. Both AST‐ and PMH‐guided therapies achieved comparable eradication rate (intention‐to‐treat analysis: 78.10% vs 74.29%, P = 0.42; per‐protocol analysis: 87.10% vs 88.64%, P = 0.80). The AST clarithromycin regimen had a lower per‐protocol eradication rate than the levofloxacin (75.47% vs 96.30%, P = 0.03) or furazolidone‐containing regimen (75.47% vs 92.75%, P = 0.02). Both groups had high compliance with low incidences of AE, and PMH‐guided therapy had a lower medical cost. Conclusions AST‐guided therapy was not superior to PMH‐guided therapy as a second‐ or third‐line treatment for H. pylori infection. Considering the cost‐effectiveness, PMH therapy is clinically more favorable.